Investigating the Construction Procedure and Safety Oversight of the Mechanical Shaft Technique: Insights Gained from the Guangzhou Intercity Railway Project - Jianwang Li; Wenrui Qi; Xinlong Li; Gaoyu Liu; Jian Chen; Huawei Tong (Buildings)
Currently, subway and underground engineering projects are vital for alleviating urban congestion and enhancing citizens’ quality of life. Among these, excavation engineering for foundation pits involves the most accidents in geotechnical engineering. Although there are various construction methods, most face issues such as a large footprint, high investments, resource waste, and low mechanization. Addressing these, this paper focuses on a subway foundation pit project in Guangzhou using mechanical shaft sinking technology. Using intelligent cloud monitoring, we analyzed the stress–strain patterns of the cutting edge and segments. The results showed significant improvements in construction efficiency, cost reduction, safety, and resource conservation. Based on this work, this paper makes the following conclusions: (1) The mechanical shaft sinking method offers advantages such as small footprint, high mechanization, minimal environmental impact, and cost-effectiveness. The achievements include a 22.22% reduction in construction time, a 20.27% decrease in investment, and lower worker risk. (2) Monitoring confirmed that all cutting edge and segment values remained safe, demonstrating the method’s feasibility and rationality. (3) Analyzing shaft monitoring data and field uncertainties, this study proposes recommendations for future work, including precise segment lowering control and introducing high-precision total stations and GPS technology to mitigate tunneling and assembly inaccuracies. The research validates the mechanical shaft sinking scheme’s scientific and logical nature, ensuring safety and contributing to technological advancements. It offers practical insights, implementable suggestions, and significant economic benefits, reducing project investment by RMB 41,235,600. This sets a benchmark for subway excavation projects in South China and beyond, providing reliable reference values. Furthermore, the findings provide valuable insights and guidance for industry peers, enhancing overall efficiency and sustainable development in subway construction.